2020
DOI: 10.3390/md18070360
|View full text |Cite
|
Sign up to set email alerts
|

Glyceroglycolipid Metabolism Regulations under Phosphate Starvation Revealed by Transcriptome Analysis in Synechococcus elongatus PCC 7942

Abstract: Glyceroglycolipids, abundant in cyanobacteria’s photosynthetic membranes, present bioactivities and pharmacological activities, and can be widely used in the pharmaceutical industry. Environmental factors could alter the contents and compositions of cyanobacteria glyceroglycolipids, but the regulation mechanism remains unclear. Therefore, the glyceroglycolipids contents and the transcriptome in Synechococcus elongatus PCC 7942 were analyzed under phosphate starvation. Under phosphate starvation, the decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
(147 reference statements)
0
2
0
1
Order By: Relevance
“…The regulatory mechanisms of MGDs are thus complex. Indeed, GlMGDs were previously observed to be regulated at the transcriptional, posttranscriptional, and post-translational levels (Awai et al, 2001;Selão et al, 2014;Shimojima et al, 2009;Xu & Miao, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The regulatory mechanisms of MGDs are thus complex. Indeed, GlMGDs were previously observed to be regulated at the transcriptional, posttranscriptional, and post-translational levels (Awai et al, 2001;Selão et al, 2014;Shimojima et al, 2009;Xu & Miao, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…La nueva clasificación de los lípidos no considera a los glucolípidos como una categoría aparte, a pesar de que esto lípidos cumplen rol importante, como parte de las membranas fotosintéticas, monogalactosildiacilglicerol y digalactosildiacilglicerol, en 80% de los lípidos del cloroplasto (Li & Yu, 2018), abundantes en las membranas fotosintéticas de las cianobacterias, como componentes bioactivos de amplio uso en la industria farmacéutica (Xu & Miao, 2020), por lo que se los ha anexado como una categoría más, en analogía y similitud química a los glicerofosfolípidos, al estar formado por glicerol, ligado por enlace éster a dos ácidos grasos, y por enlace glucosídico a un azúcar, formando un gliceroglucolípido .…”
Section: Gliceroglucolípidosunclassified
“…Glyceroglycolipids are widely distributed in plants, microalgae, and cyanobacteria and present bioactivities and pharmacological activities and can be widely used in the pharmaceutical industry. A study by Xu and Miao [18] provided further insights into the glyceroglycolipid metabolism, as well as the scientific basis for glyceroglycolipid synthesis optimization and cyanobacteria glyceroglycolipids utilization via metabolic engineering. The authors showed that there are 12 differentially expressed transcriptional regulators that could be potential candidates related to glyceroglycolipid regulation, according to a transcriptome analysis.…”
mentioning
confidence: 99%